The Effect of Perlan and Bud Management on Growth, Lateral Shoots, and the Precocity of Cherry Nursery Trees - Toprak, R.; Soysal, D.; Demirsoy, H. (Turkiye Klinikleri Journal of Medical Sciences Talapapa Bulvary no. 102 Hamammonu 1 06230, 2018)
The sweet cherry tree shows an acrotonic growth habit and grows as a forest wood. Apical dominance is important in sweet cherries and commercial growth is not possible without human intervention. It is thus difficult to obtain a good tree shape and enough shoots and leaves for quality and a plentiful crop in cherry trees. For this reason, many studies have been carried out in cherries to obtain enough lateral shoots and leaves using different methods. These procedures included Perlan application, pruning (heading), bud management (bud selection, bud removal), girdling, notching, and scoring. The present study aimed to encourage leaf and shoot growth by various applications such as Perlan (BA+GA4+7), bud management, and bud management + Perlan in sweet cherries in 2015-2017. The Perlan, bud management, and bud management + Perlan applications were applied to trees of the Regina/CAB 6P combination just before bud break. These applications affected the diameter, length and number of primary shoots on the leader, number of 2-year-old shoots bearing fruit, and also the leaf area. Besides this, the applications affected tree volume. In general, the best results in terms of features were from bud management + Perlan. © TÜBİTAK.
Keywords: Ba+Ga4+7; Branching; Bud Removal; Prunus avium L; Tree Development